Improving Forest Management: A Case Study of DENR-CAR’s Turned-over Logs - Tauli-Calugan, Beberly (Journal of Interdisciplinary Perspectives, 2025)
The Department of Environment and Natural Resources in the Cordillera Administrative Region (DENR-CAR) is committed to enhancing sustainable forest management practices, particularly concerning the utilization of turned-over logs derived from Tree Cutting Permits (TCPs). Recognizing the importance of optimizing resource use and minimizing environmental impact, this study examines current policies and practices surrounding these logs, seeking opportunities for improvement and greater efficiency. While existing guidelines, such as DAO 2003-18 and MMO 162, provide a valuable foundation, this research explores how to strengthen implementation further and ensure equitable utilization. A qualitative case study methodology was employed, utilizing semi-structured interviews with key stakeholders, document analysis, and thematic analysis to gather and interpret data effectively. The approach provided in-depth insights into the systemic challenges hindering effective log management, including unclear regulatory definitions, inefficient data tracking, absence of designated custodians, and weak enforcement mechanisms. The study's findings reveal a critical need for policy enhancements encompassing (1) implementing a prepayment mechanism for TCPs to streamline processes and reduce bureaucratic delays, (2) designating barangay Local Government Units (LGUs) as custodians to ensure localized and traceable management, and leveraging technology for efficient data monitoring and decision-making; and (4) fostering community participation in log utilization projects —such as school infrastructure and community development initiatives—ensures equitable benefits while promoting local stewardship. Strengthened monitoring and enforcement mechanisms and capacity building for relevant agencies are also proposed to mitigate non- compliance and resource misuse. This holistic framework offers actionable insights to improve log governance in CAR, promoting transparency, accountability, and technology-driven processes to achieve sustainable forest management and contribute to broader conservation goals.